The Complexities of Intimate Partner Violence: Mental Health, Disabilities, and Child Abuse History for White, Indigenous, and Other Visible Minority Canadian Women - Tutty, Leslie M. (Journal of interpersonal violence, 2021)
This research examines how mental health issues associated with intimate partner violence (IPV) relate to women’s intersecting identities of race/ethnicity, disability status, and child abuse history. Data (N = 595) from a Canadian triprovincial study included women who were White (n = 263, 44.8%), Indigenous (n = 292, 49.7%), or visible minority (n = 32, 5.5%). Few demographic differences were found. None of the mental health measures (Symptom Checklist–Short Form [SCL-10], Centre for Epidemiological Studies–Depression [CES-D-10], Posttraumatic Stress Disorder [PTSD] Checklist) were in the clinical ranges. In a MANCOVA on the mental health scales, with IPV severity, racial group, disability status, and child abuse history as variables, only disability was significantly associated with more mental health symptoms.